Intranasal Budesonide and Quality of Life in Pediatric Sleep-Disordered Breathing: A Randomized Controlled Trial. (April 2018) - Gudnadottir, Gunnhildur; Ellegård, Eva; Hellgren, Johan
Objective: To study the efficacy of budesonide nasal spray on the health-related quality of life and symptoms among children with sleep-disordered breathing. Study Design: Randomized, parallel, double-blind, placebo-controlled trial. Setting: Tertiary referral center. Subjects and Methods: Sixty children (ages, 4-10 years) who were referred because of snoring and/or apneas for >3 months were included between January 2015 and June 2016 and randomized in a double-blind design to treatment with 64 μg/mL of budesonide nasal spray (n = 30) or placebo nasal spray (n = 30) twice daily for 6 weeks. The primary outcome measurement was the change in the mean OSA-18 total score from baseline. Other variables examined were individual OSA-18 domains, a visual analog scale for quality of life, symptoms (snoring, apneas, and nasal obstruction), and adenoid and tonsil size. The trial was investigator initiated and not sponsored by the pharmaceutical industry. Results: Fifty-five children completed the trial. An intention-to-treat analysis revealed a significantly greater improvement in the mean OSA-18 total score after treatment with budesonide than placebo (19.5 vs 7.5, P = .0014). Intranasal budesonide also improved 2 OSA-18 domains (sleep disturbance, caregivers' concerns), the visual analog scale score for quality of life, as well as snoring, apneas, and nasal obstruction. No serious adverse events were reported that could be linked to the treatment. Conclusion: Among children with sleep-disordered breathing, 6 weeks' treatment with intranasal budesonide significantly improved quality of life and symptoms as compared with placebo nasal spray.